2022
DOI: 10.1101/2022.08.09.503333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural Basis of Mammalian Respiratory Complex I Inhibition by Medicinal Biguanides

Abstract: The molecular mode of action of metformin, a biguanide used widely in the treatment of diabetes, is incompletely characterized. Here we define the inhibitory drug-target interaction(s) of a model biguanide with mammalian respiratory complex I by combining cryo-electron microscopy and enzyme kinetics. We explain the unique selectivity of biguanide binding to different enzyme states. The primary inhibitory site is in an amphipathic region of the quinone-binding channel and an additional binding site is in a pock… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…These data are in line with recent studies in which metformin has been shown to curb other metabolic pathways such as gluconeogenesis from lactate and glycerol [32] and fatty acid oxidation [67], or to target other mitochondrial enzymes, such as F 1 F o ATP synthase [33] and glycerophosphate dehydrogenase (mGPDH) [32,34,35]. Moreover, the recent release of mammalian CI structures binding IM1761092, a more complex and hydrophobic phenformin derivative that has a higher inhibitory activity on CI, revealed that biguanides are able to bind at least three sites in deactive CI explaining the non-competitive behaviour of these molecules [68], but also raising questions regarding their specificity and potency. Importantly, our results can contribute to explain the conflicting data obtained in clinical trials on the use of metformin as an anti-cancer drug for different neoplasias [20][21][22][23]27,29,30,60], which may express diverse levels of additional yet unknown molecular targets.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in line with recent studies in which metformin has been shown to curb other metabolic pathways such as gluconeogenesis from lactate and glycerol [32] and fatty acid oxidation [67], or to target other mitochondrial enzymes, such as F 1 F o ATP synthase [33] and glycerophosphate dehydrogenase (mGPDH) [32,34,35]. Moreover, the recent release of mammalian CI structures binding IM1761092, a more complex and hydrophobic phenformin derivative that has a higher inhibitory activity on CI, revealed that biguanides are able to bind at least three sites in deactive CI explaining the non-competitive behaviour of these molecules [68], but also raising questions regarding their specificity and potency. Importantly, our results can contribute to explain the conflicting data obtained in clinical trials on the use of metformin as an anti-cancer drug for different neoplasias [20][21][22][23]27,29,30,60], which may express diverse levels of additional yet unknown molecular targets.…”
Section: Discussionmentioning
confidence: 99%